Suicídio e ideação suicida: um olhar psicossocial no contexto da segurança pública - Oliveira, Erik Francisco Silva de (2023)
Abstract: Suicide is a multifaceted phenomenon that affects all social strata. Considered a serious global public health problem. Suicidal ideation is the initial suicidal behavior, which, if not properly managed, can culminate in a fatal outcome. The multi-causal character of this phenomenon makes several branches of scientific knowledge such as psychology, history, sociology, philosophy, science of religions, psychiatry, biology, collective health, public security, among others, to focus on this theme in an attempt to understand, explain and prevent it. In Brazil, the suicide of public security professionals has drawn attention, professionals who in the exercise of their work are constantly confronted with accidents, tragedies and disasters, which involve violence, suffering, death and risk to their own lives. In this dissertation, suicide and suicidal ideation were investigated with public security professionals in the state of Paraíba through the Theory of Social Representations (TRS), where it was possible to access the network of interpretations and meanings, shared by these social actors, who built practical and multifaceted knowledge on the subject. Thus, this dissertation aimed to identify the social representations related to suicide and suicidal ideation in public safety professionals. Structurally, it was divided into two parts, the first consisting of theoretical chapters and the second consisting of three empirical studies guided by TRS. 277 professionals participated in the study, who answered the sociodemographic questionnaire and other instruments according to the objectives of each study. The first study aimed to apprehend the semantic fields regarding the inducing stimuli: suicide, suicidal ideation, my profession and myself. The sample consisted of 178 professionals, including military firefighters (40%), military police (46%) and civil police (14%), 48% of the sample aged between 18 and 28 years. Data were collected through the Free Word Association Technique (TALP), processed by Microsoft Excel and Tri-DeuxMots and interpreted by Factor Correspondence Analysis (CFA). The results indicated consensual representations between suicide, suicidal ideation, associated with negative aspects. The profession brought ambiguous elements that expressed satisfaction and illness. The stimulus myself was associated with positive elements. The second study aimed to identify which psychosocial factors are related to suicide and suicidal ideation in the view of public safety professionals. 228 professionals made up the sample, 175 men and 53 women, including military firefighters (45%), military police (44%) and civil police (10%), 44% of the sample aged between 29 and 39 years. Data were collected through semi-structured interviews, processed by Microsoft Excel and Alceste software and analyzed by descending hierarchical classification (CHD) and word cloud. The following axes of meaning emerged: suicide risk factors, suicide prevention measures and self-protection strategies against suicide. The results made it possible to highlight the factors that would lead to suicidal ideation and suicide, with emphasis on anchoring in the professional field, prevention factors, anchored in psychological science and spirituality, and even self-protection factors against suicide, anchored in the psychosocial field, psychoaffective and spiritual. The third study aimed to evaluate the level of suicidal ideation of public safety professionals. The study sample consisted of 277 professionals, 214 men and 63 women, including military firefighters (44%), military police (44%) and civil police (12%), 43% of the sample aged between 29 and 39 years. They responded to the Multi-Attitudinal Suicide Tendency Scale (EMATS). The Data were processed using SPSS software, version 22. The results show that there was no significant difference between professions or between genders, with the general sample having a mild level of suicidal ideation. However, in a detailed analysis, some professionals showed a severe level of suicidal ideation. Finally, it is expected that the results of this dissertation will help public security managers in the planning and implementation of public policies aimed at the mental health of professionals in this segment.